Expectant mothers and fathers' knowledge of nurturing care in a developing country - Soysal Cimen, Hafize; Karaaslan, Bedriye Tugba (Frontiers in Pediatrics, 2022)
Background: The Nurturing Care Framework (NCF), which has been emphasized by the World Health Organization (WHO) in recent years and is among the United Nations Sustainable Development Goals (SDGs), expresses the conditions created to promote early childhood development (ECD). These conditions aim to provide opportunities for children in the Good Health, Adequate Nutrition, Responsive Caregiving, Security and Safety, and Opportunities for Early Learning (5 Components) by caregivers, primarily from low and middle-income countries (LMICs). The aim of this study is to examine the knowledge and awareness of expectant mothers and fathers in Turkey, about the NCF. Methods: In this study, a cross-sectional, analytical research design was used. Nurturing Care (NC) knowledge and awareness levels of expectant mothers and fathers in the 2nd and 3rd trimesters of pregnancy were determined via the online form of “The Knowledge of Nurturing Care Inventory (KNCI)” prepared by the researchers. This form consists of 60 questions describing the 5 components mentioned above. The sample contains a total of 103 people, 91 (88.3%) women, and 12 (11.7%) men. Results: Among the findings, the highest mean of knowledge level (13.76±1.22) was found in Responsive Caregiving, and the lowest mean of knowledge level (4.35±1.83) was found in Opportunities for Early Learning. The general level of knowledge on NC was found to vary statistically significantly depending on gender in favor of the women [t(101)=3.27, p<.05], depending on educational status in favor of those with university and graduate education [F(2, 100)=3.481, p<.05], depending on participation in pregnancy school training in favor of those who attended [t(101)=2.349, p<.05], and depending on knowledge on how to support development in favor of those who know how to support [t(101)=2.370, p<.05]. Conclusions: As a result, expectant parents need information and support about the period when children can acquire the basic developmental milestones and about the developmental risk indicators. More research is needed to implement the NCF starting from the preconception period, especially in LMICs, so that the opportunities in early childhood (which is the time period when the brain architecture is shaped, and development is the fastest) are not missed.